STRATEGI PONDOK PESANTREN DALAM MENGHADAPI TANTANGAN GLOBALISASI (STUDI KASUS DI PONDOK PESANTREN API ASRI TEGALREJO MAGELANG) - Ayu Suci Rianingsih Hairiyah (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2020)
Globalization is something we cannot avoid, and it impacts on all fronts, both positive and negative impacts. Globalization can also be a challenge for all, consequently, it requires a smart strategy to face the challenges of globalization. One of them is Pesantren. Pesantren with their classic characteristics must have a strategy to adapt to today’s guidance so that it able to maintain the existence, survive and be accepted by an increasingly advanced society. One of the pesantren that is aware of this is the API ASRI Islamic boarding school in the city of Magelang, this salaf-style pesantren has proven to be able to compete with other Islamic boarding schools, although it has only been established for about 13 years, but it has become the reference boarding school throughout Indonesia. This has attracted research attention to find out what the challenges of globalization are facing the API ASRI Islamic boarding school and how the strategy of the API ASRI Islamic boarding school in facing the challenges of globalization. This research is a case study research, using a qualitative descriptive approach. In this study, researchers used several techniques and data collection instruments, namely observation, interviews, and documentation. Techniques to check the validity of the data used in this study. The result of this study is that the biggest challenge faced by API ASRI Islamic boarding school is sophistication and promiscuity. Both of these are challenges of globalization that make Islamic boarding schools prepare themselves for this. Furthermore, the strategy used is through the formation of the character of the students and the formation of skills of the students. In terms of character building through the existence of Pesantren organizations and activities including the recitation, congregational prayer and mujahadah. And in terms of skill formation includes establishing formal schools and the existence of extracurricular activities which include English, tambourine and calligraphy.